Dual effects of molybdenum on mouse oocyte quality and ovarian oxidative stress. (December 2013) - Zhang, Yu-Ling; Liu, Feng-Jun; Chen, Xiao-Li; Zhang, Zi-Qiang; Shu, Run-Zhe; Yu, Xue-Li; Zhai, Xiao-Wei; Jin, Li-Jun; Ma, Xue-Gang; Qi, Qiao; Liu, Zhi-Jie
<x xml:space="preserve">Abstract</x> A sub-acute toxicity test was performed to investigate the effects of molybdenum (Mo) on ovarian function. ICR adult female mice were exposed to Mo by free access to distilled water containing the Mo at 5, 10, 20, and 40 mg/L for 14 days. Compared to the control group, M II oocyte morphology, ovary index, and ovulation improved within the 5 mg/L Mo group, but were negatively affected by Mo at 40 mg/L. Morphologically abnormal ovarian mitochondria were observed at ≥ 20 mg/L. These alterations accompanied the changes in superoxide dismutase (SOD), glutathione peroxidise (GPx), and malondialdehyde (MDA) levels in ovaries. In conclusion, Mo affects oocyte quality possibly through regulating ovarian oxidative stress in a dose-dependent manner. It appears that Mo may improve ovarian function at a suitable concentration, which might be a candidate for the treatment of female infertility.